Dialética singular-particular-universal: Implicações do método materialista dialético para a psicologia - Pasqualini, Juliana Campregher [UNESP]; Martins, Lígia Márcia [UNESP] (My University, 2015)
Considering that Cultural-Historical theory has been gaining importance within Brazilian Psychology in the last decades, this essay aims at contributing to understanding its ontological and epistemological foundations, introducing the concepts of singularity, particularity and universality of the dialectics that exists between them. The analysis looks to explore the implications to Psychology, both as a science and as a professional practice, of the lukacsian indication about the need to apprehend the connections between singularity, particularity and universality as a condition for understanding the essence of phenomena. In that sense, this analysis brings light to the individual/society dynamics unity affirmed by historical-dialectical materialism, which contributes to overcoming of the dichotomies usually established between the poles of this relationship.
Dialectics between singularity-particularity-universality: The implications of the materialist dialectical method to psychology
Keywords: Cultural-historical psychology; Dialects; Singular-particular-universal